Are debt collection agencies truly acyclical and crisis-proof? - Mikutowski, Mateusz (Research Papers in Economics and Finance, 2025)
This paper examines the resilience of debt collection agencies during economic downturns and financial crises, challenging the notion that the industry is acyclical. The motivation stems from a gap in academic literature assessing how economic cycles impact debt collectors’ financial performance. Using a combination of case study analysis and statistical methods, the study evaluates the financial results and stock returns of 13 publicly listed debt collection companies over two major crises: the 2007–2009 financial crisis and the COVID-19 pandemic. Findings reveal that while the industry slows during crises, it is not immune. The contribution lies in providing new insights into the cyclical vulnerability of this under-researched sector.